Akal, Wahyu, Dan Toleransi: Menggali Ulang Relevansi Maturidiyah di Era Kontemporer - R, Rahmatullah; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper examines Maturidiyah theology as a branch of Sunni Islamic theology that integrates reason and revelation. Rooted in the thoughts of Imam Abu Mansur al-Maturidi, Maturidiyah emphasizes moderation and tolerance, making it relevant for addressing contemporary challenges such as radicalism, pluralism, and religious freedom. Through its rational approach, Maturidiyah offers a balanced perspective between human freedom and divine decree. This study demonstrates that Maturidiyah principles can provide a foundation for a moderate and adaptive Islamic thought in the modern era.